Aktivitas Antimalaria dan Skrining Fitokimia Metabolit Sekunder Kayu Batang dan Kulit Akar Artocarpus Camansi Blanco (Moraceae) - ALIEFMAN HAKIM; EKA JUNAIDI; BAIQ FARA DWI RANI SOFIA; YUNITA ARIAN SANI ANWAR (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
Malarial parasite, Plasmodium, has been reported resistant to commonly used antimalarial drugs, such as chloroquin. Plants Artocarpus genus are known to have high content of flavonoids. One of interesting bioactivities of Artocarpus flavonoids is their antimalarial activity. This research is to investigate the potency of secondary metabolites in the heartwood and root bark of Artocarpus camansi Blanco as an antimalarial agent. Antimalarial activity from methanol extract of heartwood and roots bark of A. camansi were tested in vitro to Plasmodium falciparum SD7 (strain sensitive to chloroquin) and W2 (strain resistant to chloroquin) The extracts were also phytochcmically screened for compounds. The result showed that the methanol extract of heartwood and root bark of A , camansi Blanco inhibited the growth of Plasmodium falciparum 3D7 strain With IC50 values of 1.84 µg/mL and 32.13 µg/mL . respectively; While similar antimalarial activity test to Plasmodium falciparum W2 strain showed IC50 valucs of 8.11 µg/mL and 17.10 µg/mL, respectively. Phytochemical screening indicated that the heartwood and root bark of A. camansi Blanco contain flavonoids, terpenoids, and tannin, while coumarin and saponins are present only in the root bark of A. camansi Blanco.